2017
DOI: 10.1667/rr14757.1.s1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Continuum of Radiation-Induced Normal Tissue Injury by a Redox-Active Mn Porphyrin

Abstract: Normal tissue damage after head and neck radiotherapy involves a continuum of pathologic events to the mucosa, tongue and salivary glands. We examined the radioprotective effects of MnBuOE, a redox-active manganese porphyrin, at three stages of normal tissue damage: immediate (leukocyte endothelial cell [L/E] interactions), early (mucositis) and late (xerostomia and fibrosis) after treatment. In this study, mice received 0 or 9 Gy irradiation to the oral cavity and salivary glands ± MnBuOE treatment. Changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Consistent with the histopathology findings, we observed gross tissue deformation in the small number of mice that died mid-way through the administration period. A recent study showed the radioprotective effects of MnBuOE on salivary glands and mouth mucosa at a maintenance dose as low as 0.1 mg/kg [43] and suggested that MnHex might have been radioprotective of hippocampal neurogenesis at much lower doses than the one we used in this study.…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with the histopathology findings, we observed gross tissue deformation in the small number of mice that died mid-way through the administration period. A recent study showed the radioprotective effects of MnBuOE on salivary glands and mouth mucosa at a maintenance dose as low as 0.1 mg/kg [43] and suggested that MnHex might have been radioprotective of hippocampal neurogenesis at much lower doses than the one we used in this study.…”
Section: Discussionmentioning
confidence: 58%
“…The impact of MnTnBuOE-2-PyP 5+ combined with radiation was demonstrated in the suppression of the FaDu human epithelial cell line from squamous cell carcinoma of the hypopharynx in a mouse sc flank xenograft model. The tumor radiosensitizing effect of MnP was discussed with regard to the significant influx of tumoricidal M1 tumorassociated macrophages [54,95]. Further, MnTnBuOE-2-PyP 5+ reduced radiation-mediated mucositis, xerostomia, and fibrosis of salivary glands.…”
Section: Molecular Pathways Affected By Mn Porphyrins In Cancer and Nmentioning
confidence: 99%
“…Another report from this team discovered that lower doses of MnBuOE mitigated cisplatin-induced oral ulcer formation, bleeding, and furfuration in the radiation area. MnBuOE did not meddle with RT/cisplatin-regulated neoplasm growth [110]. BMX-001 is undergoing phase I clinical trials concerning its safety and pharmacokinetic and radiation protection in conditions of locally advanced head and neck cancer (clinical trial number: NCT02990468).…”
Section: Modulate Ros Generation and Elimination Tomentioning
confidence: 99%